Photo differential scanning calorimetry, UV thermal mechanical analysis and UV dynamic mechanical analysis of light cured acrylics - Chonkaew, W.; Dehkordi, P.; Menard, K. P.; Brostow, W.; Menard, N.; Gençel, Osman; Gençel, Osman (Maney Publishing, 2013)
Polymers and composites cured by ultraviolet light exhibit similar shrinkage on curing as those cured by heat, with the associated distortion in the product shape. We report results pertaining to the effects of light intensity and temperature on the properties of the cured acryl resin materials. Ultraviolet differential scanning calorimetry and ultraviolet dynamic mechanical analysis were performed. The degree of distortion was measured by the displacement of the static probe position in the dynamic mechanical analysis. The results are represented as time-intensity-transformation diagrams and as three-dimensional plots of intensity, temperature and time. The largest distortion is seen when high intensity light is used to cure the sample through the gelation point. Curing the sample using low intensity light until gelation and then completing the cure at higher intensities result in minimal distortion.
Keywords: Polymer Curing; Curing Shrinkage; Differential Scanning Calorimetry; Dynamic Mechanical Analysis; Time-Intensity-Transformation Curing Diagram; Uv Curing